Best Answer

Assuming you meant 7n (not just 7 at the end of your question) - first... simplify the equation. Numbers raised to powers get priority - so your new sum is... 5n - 64n + 25n + n + 7n.... This simplifies to... -26n

Q: What is 3n squared minus 5n minus 4n cubed plus 5n squared plus n plus 7?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3n2-8n+4 = (3n-2)(n-2) when factored

3(3n - 1)(n + 1)

3n2 - 7n = 0 n(3n - 7) = 0 So either n = 0 or 3n-7 = 0 ie, either n = 0 or n = 7/3 = 21/3 = 2.33...

3n2 + 2n - 5That's a second degree trinomial expression that represents a number. The numberit represents depends on the value of 'n', and it changes whenever 'n' changes, butit's never less than -51/3 .Both the expression and the number are the product of (3n + 5) and (n - 1) .

(9n2 - 121) = (3n + 11) (3n - 11)

Related questions

3n2-8n+4 = (3n-2)(n-2) when factored

3n+2 + (3n+3 - 3n+1) = 3n+1+1 + (3n+1+2 - 3n+1) = 3*3n+1 + (9*3n+1 - 3n+1)= (3+9-1)*3n+1 = 11*3n+1.

(3n)2 = 9n2

It is a algebraic expression which can be simplified depending on the plus or minus values of 3n and 10n which have not been given.

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals", "squared", "cubed" etc. Please use "brackets" (or parentheses) because it is impossible to work out whether x plus y squared is x + y2 of (x + y) 2.

(4n - 1)(3n + 2)

3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (4) = 3n + 6

5m+2n, n-3m, 7-3n (5m+2n)+(n-3m)+(7-3n)=2m+7

3(3n - 1)(n + 1)

3n+2+3n+2=6n+4

3n2 - 7n = 0 n(3n - 7) = 0 So either n = 0 or 3n-7 = 0 ie, either n = 0 or n = 7/3 = 21/3 = 2.33...

The GCF is 3n.